Cultivation And Sporulation Of Bacillus Species In Self Healing Concrete A Systematic Literature Review_Lam Wen Siang - Lam, Wen Siang (Universiti Sains Malaysia, 2021)
Concrete repair and remediation work almost inevitable in most concrete structures. Active treatment is the solution which is bacteria (Bacillus species), widely adopted in the new sustainable concrete (self-healing concrete) to provide a more efficient and better life cost in terms of its overall structure. To allow self-healing concrete to be more commercialized, the factor, media used to produce the microbial species need to be precisely addressed accordingly. The main aims of this review are to provide information regarding the method of cultivation and sporulation of Bacillus species in self-healing concrete and the method to identify its performance to obtain the optimum condition. This review is planned according to (Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) to prevent any unbiased and increase the reliability of the data extracted and synthesis. Furthermore, there are a total of 11 papers included in this review associate with other supplementary material through cross-referencing. All of these paper data were extracted based on its general information, bacteria, experimental setup, evaluation of healing, and experimental result. Although bacteria strains are applied in each experiment, its response to the factor showed almost similar results in terms of pH, oxygen supply, temperature, culture medium, and nutrient. A suitable medium is crucial in every stage (growth, reproduction, precipitation), as it can maximize the performance of the self-healing concrete. Only with suitable evaluation techniques, a designer can formulate an optimized microbial self-healing concrete recipe. However, there are more possibilities of formulating microbial self-healing concrete which is not restrained to Bacillus species only. This review followed the recent last 5 years of research (2016-2020) on the engineering field, more other potential microbial species are yet to be discovered in the future.